A newly identified Minute locus, M(2)32D, encodes the ribosomal protein L9 in Drosophila melanogaster. - Schmidt, A.; Hollman, M.; Schäfer, U. (Molecular and General Genetics, 1996)
A gene encoding a ubiquitously expressed mRNA in Drosophila melanogaster was isolated and identified as the gene for ribosomal protein L9 (rpL9) by its extensive sequence homology to the corresponding gene from rat. The rpL9 gene is localized in polytene region 32D where two independent P element insertions flanking the locus are available. Remobilization of either P element generated lines with a typical Minute phenotype, e.g. thin and short bristles, prolonged development, and female semisterility in heterozygotes as well as homozygous lethality. All these characteristics can be rescued when a 3.9 kb restriction fragment containing the rpL9 gene is reintroduced by P element-mediated germline transformation. This result confirms that M(2)32D codes for ribosomal protein L9.